2003
DOI: 10.1002/uog.938
|View full text |Cite
|
Sign up to set email alerts
|

Spatial velocity profile changes along the cord in normal human fetuses: can these affect Doppler measurements of venous umbilical blood flow?

Abstract: Objective Several studies have assumed a parabolic velocity profile through the umbilical vein (UV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…Because less susceptible to error than intensity weighted mean velocity, we used the time averaged V max corrected by a velocity profile factor for flow calculation. The assumption that the velocity profile is parabolic, i.e., h ϭ 0.5, may not be valid under all conditions (38). However, three recent publications showed excellent agreement between both methods for flow calculation in the UV (14,22) and the PV (18), which is reassuring for the method applied in this study.…”
Section: Discussionmentioning
confidence: 55%
“…Because less susceptible to error than intensity weighted mean velocity, we used the time averaged V max corrected by a velocity profile factor for flow calculation. The assumption that the velocity profile is parabolic, i.e., h ϭ 0.5, may not be valid under all conditions (38). However, three recent publications showed excellent agreement between both methods for flow calculation in the UV (14,22) and the PV (18), which is reassuring for the method applied in this study.…”
Section: Discussionmentioning
confidence: 55%
“…For the estimation of volume blood flow, we used two concepts of velocity measurement: the VWMEAN1 and the TAMXV, corrected by a factor according to the velocity profile in the vessel17. Both concepts have potential sources of error37, 38. We used 0.5 TAMXV to calculate the volume flow, assuming a parabolic velocity profile in the main portal stem, and had an internal control by using VWMEAN for the flow calculation; we found virtually no difference between them, indicating that both methods can be used interchangeably.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of the color Doppler cineloop technique is that measuring the maximum velocity from the entire cross‐sectional vessel area rather than from a small sample volume provides the operator with a better chance of determining the correct maximum velocity in the vessel area of interest. In fact, Pennati et al 25 demonstrated recently that the velocity profile in the umbilical vein is not perfectly parabolic and varies at different sites of the cord, and that the maximum flow velocity is not always situated in the center of the vessel. The color Doppler cineloop technique allows the interrogation of a large cross‐sectional vessel area without the interference of blood flow in adjacent vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary to accurate measurement of the vessel size, it is essential to obtain the correct value for the maximum flow velocity in the area of interest. Recently, it was demonstrated that flow velocity profiles in the umbilical vein are not perfectly parabolic and that the maximum velocity is not always in the center of the vessel25. While with spectral Doppler analysis it is possible to calculate the maximum flow velocity from a small sample volume, the color Doppler cineloop recording technique with offline analysis provides better conditions to determine the correct maximum flow velocity because it includes the entire vessel area.…”
Section: Introductionmentioning
confidence: 99%